Simultaneous measurement of the neutron- and proton-induced fissions by activation detectors. (November 2019) - Wojciechowski, A.; Voronko, V.; Sotnikov, V.; Zhadan, A.
Highlights: Describing experiment was performed in Dubna in QUINTA assembly. The experimental fission products are measured by activation detectors. Calculating the fission yield of fission product for proton-induced fissions. Estimating the measured number of neutron- and proton-induced fissions. Comparing the experimental data with predicted results from MCNPX code. Abstract: This work is a next step toward the study of physical properties of the Accelerator Driven System (ADS) in which a deeply subcritical active core (512 kg natural uranium target) is irradiated by a pulsed beam of relativistic particles. The measurement of the total number of fission reactions is a fundamental task in the given research. The estimated method of determining the number of fission reactions based on activation detectors is analyzed. Our interest has been focused on the study of the proton- and neutron-induced fission reaction inside the high-energy particle beam volume. The fission products of fission reactions have been measured employing natural uranium activation detectors and germanium gamma detectors (HPGe). Experimental data are taken from the QUINTA experiment performed at JINR, Dubna, in November 2014. The presented method gives an effective possibility of estimating the measured number of fission reactions induced by neutrons and high-energy protons simultaneously.